Oral Supplementation of Glucosamine Fails to Alleviate Acute Kidney Injury in Renal Ischemia-Reperfusion Damage - Johnsen, Marc (PLoS One, 2016)
Acute kidney injury is a leading contributor to morbidity and mortality in the ageing population. Proteotoxic stress response pathways have been suggested to contribute to the development of acute renal injury. Recent evidence suggests that increased synthesis of N-glycan precursors in the hexosamine pathway as well as feeding of animals with aminosugars produced in the hexosamine pathway may increase stress resistance through reducing proteotoxic stress and alleviate pathology in model organisms. As feeding of the hexosamine pathway metabolite glucosamine to aged mice increased their life expectancy we tested whether supplementation of this aminosugar may also protect mice from acute kidney injury after renal ischemia and reperfusion. Animals were fed for 4 weeks ad libitum with standard chow or standard chow supplemented with 0.5% N-acetylglucosamine. Preconditioning with caloric restriction for four weeks prior to surgery served as a positive control for protective dietary effects. Whereas caloric restriction demonstrated the known protective effect both on renal function as well as survival in the treated animals, glucosamine supplementation failed to promote any protection from ischemia-reperfusion injury. These data show that although hexosamine pathway metabolites have a proven role in enhancing protein quality control and survival in model organisms oral glucosamine supplementation at moderate doses that would be amenable to humans does not promote protection from ischemia-reperfusion injury of the kidney.